2023
DOI: 10.2217/imt-2022-0168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PD-L1 as a Biomarker for Immunotherapy for Hepatocellular Carcinoma: Systematic Review and Meta-Analysis

Abstract: Aim: To determine if PD-L1 can be used as a biomarker to predict the efficacy of anti-PD-1/PD-L1 inhibitors in hepatocellular carcinoma (HCC). Methods: Relevant studies from a specific search of the four databases from October 2014 to December 2022 were included in this meta-analysis. Results: Higher PD-L1 expression levels were associated with a higher objective response rate (ORR). Higher PD-L1 expression levels on tumor cells and tumor proportion score were associated with higher ORR. PD-L1 was capable of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A phase II clinical trial of pembrolizumab in patients with unresectable advanced HCC suggested that there was no significant correlation between PD-L1 positivity and treatment response [ 35 ]. However, Zhou et al reported a meta-analysis study showing that positive PD-L1 expression is better associated with ORR in patients with advanced liver cancer treated with anti-PD-1/PD-L1 [ 36 ]. Therefore, the expression of PD-L1 is currently controversial in predicting the efficacy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II clinical trial of pembrolizumab in patients with unresectable advanced HCC suggested that there was no significant correlation between PD-L1 positivity and treatment response [ 35 ]. However, Zhou et al reported a meta-analysis study showing that positive PD-L1 expression is better associated with ORR in patients with advanced liver cancer treated with anti-PD-1/PD-L1 [ 36 ]. Therefore, the expression of PD-L1 is currently controversial in predicting the efficacy of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis suggested that higher PD-L1 expression levels on tumor cells and tumor proportion score were associated with a higher ORR in HCC patients treated with ICIs (73). Another meta-analysis confirmed improved ORR in PD-L1-positive patients compared to PD-L1-negative patients (26% vs. 18%, OR=1.86).…”
Section: Pd-l1mentioning
confidence: 96%
“… 244 Using meta‐analysis, Zhou et al. 245 discovered that high expression of PDL1 in tumor cells instead of tumor tissues was associated with better prognosis, and PDL1 could be used as a prognostic biomarker of immunotherapy efficacy for HCC.…”
Section: Cancer Immunotherapy: Inhibitor Applications Clinical Trials...mentioning
confidence: 99%
“…A recent study showed that the expression of PDL1, B7‐H3 and VISTA as well as some tumor necrosis factor receptor superfamily such as OX40L, CD27, 4‐1BB, CD40, and CD95/Fas were correlated with the head and neck squamous cell carcinoma immunotherapy efficiency, and could serve as potential biomarkers to predict the immunotherapy response 244 . Using meta‐analysis, Zhou et al 245 . discovered that high expression of PDL1 in tumor cells instead of tumor tissues was associated with better prognosis, and PDL1 could be used as a prognostic biomarker of immunotherapy efficacy for HCC.…”
Section: Cancer Immunotherapy: Inhibitor Applications Clinical Trials...mentioning
confidence: 99%